Answer:
x = i and x = i
![√(5)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6t5afeluhyfr0smmu6fxh4zbtmnt6101i5.png)
Explanation:
Given
+ 6x² + 5 = 0
Using the substitution u = x², then
u² + 6u + 5 = 0 ← in standard form
(u + 1)(u + 5) = 0 ← in factored form
Equate each factor to zero and solve for u
u + 1 = 0 ⇒ u = - 1
u + 5 = 0 ⇒ u = - 5
Convert solutions back into terms of x
x² = - 1 ⇒ x =
= i
x² = - 5 ⇒ x =
= i
![√(5)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6t5afeluhyfr0smmu6fxh4zbtmnt6101i5.png)